Effects of self-control of feedback timing on motor learning - Akizuki, Kazunori; Takeuchi, Kosuke; Yabuki, Jun; Yamaguchi, Kazuto; Yamamoto, Ryohei; Kaneno, Tatsuya (Frontiers in Psychology, 2025)
IntroductionAlthough the effects of self-control on motor learning have been well studied, the effects of self-controlled feedback timing have not been thoroughly investigated. Therefore, this study aimed to examine the effects of self-controlled feedback timing on motor learning through two experiments.MethodsIn Experiment 1, participants were randomly assigned to one of three groups: concurrent feedback, terminal feedback, or self-controlled feedback. The procedure included a pre-test, practice session, and a retention test conducted 1 week after the practice, with visual feedback provided only during the practice session. Participants also completed three subscales of the Intrinsic Motivation Inventory before/after the practice session and the NASA-Task Load Index (NASA-TLX) after the practice session. In Experiment 2, participants were randomly assigned to either a self-controlled feedback group or a yoked feedback group, following the same procedure as in Experiment 1.ResultsIn Experiment 1, the concurrent feedback group demonstrated the smallest performance errors during practice, while the terminal feedback group showed the largest performance errors. However, both the self-controlled and terminal feedback groups exhibited significantly smaller errors than the concurrent feedback group in the retention test. In Experiment 2, the self-controlled group made significantly fewer errors than the yoked group in the retention test. The self-controlled group showed significantly higher intrinsic motivation and significantly lower scores in the performance subscale of NASA-TLX than the yoked group.ConclusionIn the present study, concurrent visual feedback interfered with motor learning by inducing a dependency on visual feedback. Our findings suggest that self-controlled feedback timing may overcome the potential negative effects of concurrent visual feedback through the positive influence of self-control, which may arise through the involvement of both intrinsic motivation and information processing.